In vivo ultrasound guided transvaginal oocyte collection in the cow - AMIRIDIS (Γ.Σ. ΑΜΟΙΡΙΔΗΣ), G. S.; SALAHEDDINE, M.; JEFFCOATE, I. A.; VAINAS (Ε. ΒΑΪΝΑΣ), E.; ROBERTSON, L. (Journal of the Hellenic Veterinary Medical Society, 2018)
This paper describes the results of the in vivo ultrasound guided follicular aspiration for ovum pick υρ (OPU) in the cow. Twelve non pregnant dry cows aged 4-6 years were used in this experiment. Eight cows underwent OPU during three successive oestrous cycles and another four cows were used as controls having only transvaginal ultrasound scanning of their ovaries. Oocyte collection took place three times during the luteal phase of each natural oestrous cycle (days 3-4,9-11 and 14-17). The content of 326 follicles with a diameter of 4-15mm was aspirated and 104 oocytes were collected (recovery rate 31.9% or 1.55 oocytes per cow and session). The oocyte recovery rate increased after the first three sessions (from 13.04% to 35.0%) and reached levels of υρ to 52.6%. More follicles were aspirated on days 9-11 (133 follicles 40.8%) compared to 111 (34%) follicles on days 14-17 and 82 (25%) on days 3-4) (P<0.05). The evaluation of the collected oocytes revealed that 60 oocytes (57.7%) were suitable for further in vitro manipulation. Neither the origin of the oocyte (left or right ovary) nor the stage of the oestrous cycle affected the recovery rate or the quality of the collected oocytes. There was no significant difference either in the length of the oestrous cycle between the experimental animals and the controls (21.6± 1.4 vs. 22.37±1.0 respectively), or in plasma progesterone concentration in daily collected blood samples from the animals of the two groups. The results of this study are compared to those from the international literature and to the results from endoscopical methods for oocyte recovery. The feasibility of application of this technique to projects designed to improve the genetic merit of cows is discussed.